Sistem Penilaian Kinerja Agroindustri Teh Kebun Bantaran PT Perkebunan Nusantara XII - Bambang Herry Purnomo; I. B. Suryaningrat; Aulia Brilliantina (Politeknik Negeri Jember, 2017)
Corporate performance can be measured financially and non-financially. Non-financial measurements cannot be separated from the financial measurements. The aims of this study was to describe of how performance measurement systems that has been conducted at tea agroindustry on Kebun Bantaran PT Perkebunan Nusantara XII to achieve success areas of tea agroindustry. The system was built to adopt from Integrated Dynamic Performance Measurement Systems (IDPMS) model. Interviews, observations, and company’s documents were conducted to gather empirical information regarding the needs of developing new appraisal system. Four integrated functional area of the models are corporate management, factory management, production line, and lab QC. Each functional areas were linked through the specification, reporting, and dynamic updating of the defined areas of success, performance measure, and performance standard. Understanding interrelatioships of performance measurements provides the foundation for more focused improvement effort.